Kuwait Environmental Remediation Program (KERP) : Limited Site Soil Characterization in South East Kuwait - Gharabally, Dhari Al-; Al-Barood, Aisha-; Sudhakaran, Binu (IJRDO - Journal of Social Science and Humanities Research, 2016)
During the 1991 -1992 Gulf War about 114 square kilometers of Kuwait’s desert environment was severely damaged by detonated oil wells at the hands of Iraqi troops leading to the largest environmental and ecological disaster in Kuwait’s history. Aerial fall-out from oil spray and combustion products from oil fires and spills combined with regional/local topographic depressions resulted in the formation of large dry oil lakes and tarcrete on the land surface. The damaged oil wells spilled crude oil across the land surface and created “Oil lakes” in low lying land. These oil lakes covered several square km of land in the northern and southern oil fields of Kuwait. Consequently, contaminated soil estimated to be around 26 Million m3 altered desert soil properties and ecological landscape, which caused the deaths of plants and/or animals; and posing a threat to the precious fresh groundwater resources. The United Nations Compensation Commission (UNCC), Kuwait National Focal Point (KNFP) and Kuwait Oil Company (KOC) cooperated in a joint project to undertake comprehensive and collaborative efforts to remediate the contaminated Soil.